1976
DOI: 10.1063/1.88963
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam-deposited polycrystalline diamondlike films

Abstract: X-ray and electron beam diffraction analyses have been carried out on thin films deposited from a beam of carbon ions. Results show that the films consist of a polycrystalline background of cubic diamond with a particle size of 50–100 Å with single-crystal regions up to 5 μm in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 316 publications
(48 citation statements)
references
References 5 publications
1
46
0
1
Order By: Relevance
“…Due to the attraction and outstanding properties of diamond as a rare material, the former of these activities is certainly the more spectacular one. Nevertheless, since the publications of Aisenberg and Chabot [2] and Spencer et al [3] amorphous carbon films with diamondlike properties have found enormous interest. These noncrystalline films are still of considerable importance since large area depOSition of homogeneous films with smooth surfaces is easily achieved on any substrate and at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the attraction and outstanding properties of diamond as a rare material, the former of these activities is certainly the more spectacular one. Nevertheless, since the publications of Aisenberg and Chabot [2] and Spencer et al [3] amorphous carbon films with diamondlike properties have found enormous interest. These noncrystalline films are still of considerable importance since large area depOSition of homogeneous films with smooth surfaces is easily achieved on any substrate and at low temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the equilibrium carbon vapor at 2500 K is composed of mono, di, and triatomic carbon 63 molecules, the latter being predominant, while even single carbon atoms do not represent suitable building blocks for diamond growth because in its ground state the carbon atom is divalent. However, excitation of the carbon vapor atoms and molecules by electron bombardment with energy around 50 eV produces excited states which are capable of forming four coordination bonds between deposited carbon atoms [23]. As a result, layers of a so-called diamond-like carbon can be obtained even at sub-zero temperatures.…”
Section: Excitation Of the Vapor Phasementioning
confidence: 99%
“…Deposition of DLC films on metal substrates in the liquid phase is seldom reported. There are experimental evidences that materials that can be deposited from the vapour phase can also be deposited in the liquid phase using electroplating techniques and vice versa [9]. Based on the observations in [10], it was suggested that camphor (C 10 H 16 O) and camphor like other precursors might be the best-suited candidates as starting materials for semiconducting carbon films for electronics applications.…”
Section: Introductionmentioning
confidence: 98%